1993
DOI: 10.1095/biolreprod48.5.952
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Weight, Sertoli Cell Number, Daily Sperm Production, and Sperm Output of Sexually Mature Rabbits after Neonatal or Prepubertal Hemicastration1

Abstract: The present study was conducted to investigate the influence of hemicastration and age at hemicastration on the subsequent testicular development of male rabbits through sexual maturity. Thirty New Zealand white rabbits were left intact or were hemicastrated on Day 35, 49, 77, or 105 postconception. Beginning at 7 mo of age, ejaculates were collected every other day for 1 mo, and the last ten ejaculates were used to quantify daily sperm output. At 8 mo, the rabbits were killed and their carcases, testes, testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…Rabbits are sexually mature at the oldest ages studied by Bredman et al [1992a], but they continue to grow and testis weight continues to increase until the age of 6 months [Thompson and Berndtson, 1993]. In their studies of earlier developing animals, Bredman et al [1992a] have shown that some isoforms of MyHCs are transiently expressed during development, and that there seems to be a trend toward more fibers expressing cardiac alpha MyHC at older ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbits are sexually mature at the oldest ages studied by Bredman et al [1992a], but they continue to grow and testis weight continues to increase until the age of 6 months [Thompson and Berndtson, 1993]. In their studies of earlier developing animals, Bredman et al [1992a] have shown that some isoforms of MyHCs are transiently expressed during development, and that there seems to be a trend toward more fibers expressing cardiac alpha MyHC at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the largest animals studied (body weight 2,000 g, approximate age = 2 months) must be considered immature. Rabbits no longer express developmental MyHC isoforms at this age, but they continue to grow until they are at least 6 months old [Thompson and Berndtson, 1993], and their MyHC isoform content may change during this period [d'Albis et al, 1993]. Whether or not the same heterogeneity of phenotypes is found in fully mature rabbits is not known.…”
Section: Abbreviations Used In This Papermentioning
confidence: 99%
“…Seven males and six females, all at least 6 months old, were used. Rabbits are sexually mature at 2 months old, but they continue to grow until they are 6 months old [Thompson and Berndtson, 1993]. All experiments were in accordance with NIH guidelines and the Institutional Animal Care and Use Committee of Emory University approved protocols for them.…”
Section: Methodsmentioning
confidence: 99%
“…Numbers of Sertoli cells in the seminiferous epithelia of knockout mice remain normal Given that testis size correlates with germ cell numbers, germ cell number depends on the number of Sertoli cells (Berndtson et al, 1987;Berndtson and Thompson, 1990;Thompson and Berndtson, 1993), and testicular enlargement can be accompanied by increased numbers of Sertoli cells (Hess et al, 1993), we next sought to determine whether Sertoli cell numbers were altered in Rbpj Fig. S8), but the overall number of Sertoli cells was not significantly different from that in the littermate control testes (Fig.…”
Section: Inactivation Of Rbpj In Sertoli Cells By Cell-specific Gene mentioning
confidence: 99%